Analisis Proses Penanganan Export dan Import di Terminal NPCT1 Tanjung Priok pada Masa Pandemic Covid 19 - Ishak Trianda; Denny Umbara (Sekolah Tinggi Manajemen Transportasi (STMT Malahayati Jakarta), 2024)
One Of The Problems In Recent Months At The Tanjung Priok Port In Jakarta, Indonesia's Largest Port, Is The Weakening Of The Flow Of Incoming And Outgoing Containers. Various Policies Have Been Implemented By The Port And The Government, One Of Which Is Regarding The Impact Of The Covid 19 Outbreak On The Handling Of Export And Import Containers At The Npct1 Terminal In The Tanjung Priok Area, Which Has Seen Its Revenue Volume Decline. This Thesis Aims To Obtain An Analysis Of The Impact Of The Covid 19 Outbreak On The Handling Of Export And Import Containers At The Npct1 Terminal In The Tanjung Priok Area. The Data Used Is Data From The Auto Gate System For The Period 1 February To 30 March 2020. By Taking Data From Customs For The New Priok Container Terminal One Tps, With The Results Of The Gate Report Per Month, The Comparison Of The Average Time Before The Covid 19 Pandemic From Entering To Leaving The Container Shows That The Reduction In The Export And Import Process Of Containers At The Npct1 Terminal Is Very Significant. By Analyzing The Export And Import Container Handling Process At The Npct1 Tanjung Priok Terminal, We Can Find Out The Development Of Containers Entering And Leaving The Terminal With A Reporting System Created By The Npct1 Terminal, So That It Is Hoped That The Operational Handling Of The Npct1 Container Terminal Will Always Continue To Operate Without Any Lock Down Because We Prioritize The Best Service Because Our Terminal Is An Asset Of The Country's Economy And We Continue To Comply With The Health Protocol For Covid-19 Regulations, Always Wear Ppe (Personal Protective Equipment) And Always Provide Hand Sanitizers, Hand Washing Equipment In Every Workplace, Always Routinely Spray Disinfectants While Working, With The Auto Gate System (Ags) Npct1 Terminal Is Ready To Compete With Several International Terminals In Tanjung Priok With Healthy Competition. Therefore, This Study Aims To Analyze The Impacts Caused By The Distribution Of The Covid-19 Coronavirus Pandemic, Especially In Indonesia, Which Is One Of The Countries That Prioritizes The International Economy In The Field Of International Container Terminal Ports.